Green Advertising Effectiveness: Brand Image and Green Trust Among Generation Y and Z - Vanessa, Jessica; Ariestya, Angga (JURNAL KOMUNIKASI INDONESIA, 2024)
Green advertising has grown exponentially over the past few decades. Although there are a lot of proenvironment attitudes, there are also signs of distrust by the public towards green advertising, which is often perceived as deceptive. For that reason, this research was done to find out the effects of green advertising on green trust mediated by brand image using the Selective Influence Theory. This research used a quantitative approach with an explanative research type, which was done using a survey with an online questionnaire. The questionnaire is distributed to 394 respondents, with quota sampling, consisting of 197 generation Z and 197 generation Y. The hypothesis was tested with path analysis using the Structural Equation Model (SEM). The result showed that green advertising is effective in influencing green trust either directly or through brand image as mediation with a large effect of 0.72. This concluded the path model as a partial mediation. From the result, it is proven that green advertising with the main focus in product orientation is effective in Generation Y and Z. Therefore, this research contributed in proving green marketing communication and selective influence theory through the effectiveness of green advertising on brand image and green trust.